Taxonomic study of Moenkhausia cotinho Eigenmann, 1908 and Hemigrammus newboldi (Fernández-Yépez, 1949) with the description of two new species of Moenkhausia (Teleostei: Characiformes: Characidae) - Mathubara, Kleber; Toledo-Piza, Mônica (Zootaxa, 2020)
Moenkhausia cotinho is redescribed based on the examination of meristic and morphometric data and external morphological characters of specimens from the Amazon and Orinoco basins and from rivers in the Guyana. The species is distinguished from congeners based on the combination of a reticulate color pattern, the presence of dark spots on the posterior edge of scales of the longitudinal rows dorsal to the lateral line, the presence of a dark blotch on the caudal-fin base failing to reach the posterior tip of the middle caudal-fin rays; the dorsal region of the eyes red to orange in life; 5/3 longitudinal series of scales, above and below the lateral line, respectively; and the tips of the pectoral-fin rays not extending beyond the base of the pelvic fin. All specimens of M. cotinho have a completely pored literal line except for a few specimens from drainages in the Guyana. The redefinition of the taxonomic limits and geographic distribution of M. cotinho allowed us to reevaluate the taxonomic limits and geographic distribution of Hemigrammus newboldi, the identity of which has been previously questioned, but which is clearly diagnosed from M. cotinho based on the relatively longer pectoral fin, the presence of conical teeth in the posterior portion of the dentary, the absence of a reticulate color pattern of body and in the shorter longitudinal dark stripe on body. In addition, two new species of Moenkhausia are described: Moenkhausia rondoni sp n. from the rio Madeira basin, Brazil and Moenkhausia pirahan sp n. from the lower rio Madeira and rio Trombetas and rio Tapajós basins, Brazil.